Primary Maternity Units in rural and remote Australia: Results of a national survey. (September 2016) - Kruske, Sue; Kildea, Sue; Jenkinson, Bec; Pilcher, Jennifer; Robin, Sarah; Rolfe, Margaret; Kornelsen, Jude; Barclay, Lesley
Abstract: Background: Primary Maternity Units (PMUs) offer less expensive and potentially more sustainable maternity care, with comparable or better perinatal outcomes for normal pregnancy and birth than higherlevel units. However, little is known about how these maternity services operate in rural and remote Australia, in regards to location, models of care, service structure, support mechanisms or sustainability. This study aimed to confirm and describe how they operate. Design: a descriptive, cross-sectional study was undertaken, utilising a 35-item survey to explore current provision of maternity care in rural and remote PMUs across Australia. Data were subjected to simple descriptive statistics and thematic analysis for free text answers. Setting and Participants: Only 17 PMUs were identified in rural and remote areas of Australia. All 17 completed the survey. Results: the PMUs were, on average, 56 km or 49 minutes from their referral service and provided care to an average of 59 birthing women per year. Periodic closures or downgrading of services was common. Low-risk eligibility criteria were universally used, but with some variability. Medically-led care was the most widely available model of care. In most PMUs midwives worked shift work involving both nursing and midwifery duties, with minimal uptake of recent midwifery workforce innovations. Perceived enablers of, and threats to, sustainability were reported. Key conclusions and implications for practice: a small number of PMUs operate in rural Australia, and none in remote areas. Continuing overreliance on local medical support, and under-utilisation of the midwifery workforce constrain the restoration of maternity services to rural and remote Australia. Highlights: Only a small number of Primary Maternity Units operate in rural Australia. Primary Maternity Units are a sustainable option for providing rural birth services. Midwifery models of care are under-utilised. Reliance on medical models impedes service sustainability in rural and remote areas.